Multiscale and Multiphysics Processes in Geomechanics Results of the Workshop on Multiscale and Multiphysics Processes in Geomechanics, Stanford, June 23-25, 2010. - Borja, Ronaldo I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Following the successful International Workshop on Modern Trends in Geomechanics held in Vienna in 2005, Stanford University hosted its sequel in 2010 under the theme Multiscale and Multiphysics Processes in Geomechanics. This book is a compilation of the extended abstracts from the Stanford workshop and highlights the diverse and complex processes encountered in geomechanics in terms of scale (from nanometer to kilometer) and scientific scope. Topics covered in this book include coupled physics phenomena such as thermo-poro-mechanical and electro-poro-mechanical processes, chemical species reactivity and transport, strain localization phenomena, unsaturated soils, fluid flow in porous solids, and dynamics of fault zones. The book also covers contributions dealing with the development of multiscale numerical techniques, as well as the laboratory and field investigation methods supporting these numerical techniques.
Experiments and constitutive models -- Multiscale processes -- Faults and discontinuities -- Applications and simulations -- Appendix.
Keywords: Engineering geology; Engineering—Geology.; Foundations; Hydraulics; Geotechnical engineering; Geophysics; Geoengineering, Foundations, Hydraulics; Geotechnical Engineering & Applied Earth Sciences; Geophysics and Environmental Physics